Interpretation of Gender Bias in QS. Al-Taubah/9 verse 71: Critical Review of Tafsir Al-Qur’an Tematik The Ministry of Religion Affairs Republic of Indonesia - Ainurrofiq, Faiq; Amir, Abdul Muiz; Widus Sempo, Muhammad (IAIN Pekalongan, 2020)
This paper aims to critically explore interpretation result of QS. Al-Taubah/9:71 in Tafsir Qur’an Tematik by The Ministry of Religion Affairs Republic of Indonesia. This conducted because it is suspected that it contains a gender bias interpretation. This research used a critical qualitative-interpretative design by investigating the interpretation of QS. al-Taubah / 9: 71 using a contextualization interpretation. The findings reveal that the Thematic Interpretation of Al-Quran by the Ministry of Religion affairs published for the first time in 2009 represents the interpretation of the QS. al-Taubah/9: 71 as legitimacy of limiting the area of political leadership for women. Therefore, the product of such interpretations tends to be bias because it limits the area of state leadership based on a particular gender. This interpretation seems to contrast with the meaning of the significance of the verse that is found through the exploration of textual, contextual-historical, and dynamic contextual approaches. The meaning of the significance obtained from this verse only discusses about the socio-spiritual relationship in the internal Muslim community, not in the political context. The same results can also be seen in Tafsir al-Wajiz, in which the work is also the interpretation of the Ministry of Religion published in 2016, as well as the interpretation of scholars in various classical commentaries. The implication of the results of the interpretation of gender bias in Tafsir Qur’an Tematik can have an impact toward government policies in positioning positions for women in the society, especially in the area of the structural leadership of the country.